The Role of Communication in Improving Mental Health of Madrasah Ibtidaiyah Students - Muhamad Hanif Fuadi; Muji Agustini; Aar Khariatul Maslamah (Insights: Journal of Primary Education Research, 2024)
This study aims to analyze the role of communication in improving the mental health of Madrasah Ibtidaiyah Cahaya Cimahi students. The focus of this study includes communication strategies carried out by teachers and parents in supporting students' mental health, as well as the impact of effective communication on students' emotional and mental well-being, including the reduction of stress, anxiety, and depression. In addition, this study identifies the role of various parties (teachers, parents, and peers) in creating a communication environment that supports mental health, as well as school programs or initiatives that have been implemented. The results of the study show that directed and supportive communication has a significant impact on improving students' mental health.